1982
DOI: 10.1111/j.1365-2672.1982.tb04378.x
|View full text |Cite
|
Sign up to set email alerts
|

Examination of bovine faeces for the isolation and identification of Clostridium species

Abstract: A total of 162 faecal samples was collected from individual cattle on ten farms from three states of Nigeria. These samples yielded 333 clostridial isolates out of which 295 (88.6%) were identified; the remaining 38 (11.4%) could not be readily identified at species level. The species most frequently isolated was Clostridium perfringens representing 63.7% of the isolates and the next highest was Cl. bifermentans with a frequency of 12.6%. The other species identified were less frequently isolated. No farm yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…These include isolations from camel, cow, donkey and horse dung,26 27 the intestinal contents of the antarctic Weddell seal,28 as part of the normal flora of conventional neonatal hares,29 and the isolation of a cytotoxigenic strain from a sitatunga deer (Grant IK, Borriello SP and Honour P, unpublished observations, 1982). There were no reports of carriage of C diffic ile in household pets and therefore the potential for disease in these types of animals, and for the transmission of the organism from animal to man either directly or via a fomite was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…These include isolations from camel, cow, donkey and horse dung,26 27 the intestinal contents of the antarctic Weddell seal,28 as part of the normal flora of conventional neonatal hares,29 and the isolation of a cytotoxigenic strain from a sitatunga deer (Grant IK, Borriello SP and Honour P, unpublished observations, 1982). There were no reports of carriage of C diffic ile in household pets and therefore the potential for disease in these types of animals, and for the transmission of the organism from animal to man either directly or via a fomite was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…For example, if it were shown to be a common member of the faecal flora of a livestock animal, it could contaminate meat at slaughter; or, if it was widely distributed in soil it could contaminate raw food such as fresh vegetables. Despite isolated reports of C. dfjcile in two sick piglets [13] and in one of 162 Nigerian cattle [14], there has not been a large survey of the prevalence of C. dijjcile in the gut of animals in the human food chain. The results of the present study suggest that consumption of beef, pork or lamb is not likely to be an important source of exposure to C. difJicile, as it was not part of the faecal flora of 104 cattle, 100 pigs and 1% of sheep.…”
Section: Discussionmentioning
confidence: 99%
“…Netherwood et al (1996) reported that C. perfringens w a s significantly associated with diarrhoea in foals, while Browning et al (1991) reported that isolation of C. perfringens was not associated with diarrhoea in foals. Clostridium perfringensassociated enteric disease is difficult to diagnose on the basis of culture alone since the organism can be found in the faeces of normal animals (Princewell and Agba 1982;Tschirdewahn et al 1991;Miwa et al 1997;Cohen and Divers 1998). Quantitative culture has been suggested as a tool to diagnose C. perfringensassociated enteric disease in horses (Wierup and DiPietro 1981;Dart et al 1988;Cohen and Divers 1998).…”
Section: Introductionmentioning
confidence: 99%